2006
DOI: 10.3164/jcbn.39.56
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress In Helicobacter pylori-Assocaited Gastroduodenal Disease

Abstract: Summary Helicobacter pylori (H. pylori) is a spiral-shaped, Gram-negative rod, which induces the infiltration to the gastric mucosa by neutrophils, macrophages, and T and B lymphocytes; however, this immune and inflammatory response cannot completely clear the bacterial infection, and leaves the host prone to complications resulting from persistent inflammation. Resultantly, H. pylori infection causes chronic inflammation, accumulation of reactive oxygen species, and oxidative DNA damage in the gastric mucosa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…8) and inhibited apoptosis (Fig. 6) in RIE-1 cells, it seems that the initial ROS production may have affected intracellular protein function, resulting in the indomethacin-induced This hypochlorous anion reacts with ammonia, derived from urea by H. pylori-associated urease, and yields a cytotoxic oxidant, monochloramine (NH 2 Cl), whose lipophilic properties allow it to freely penetrate biological membranes to oxidize intracellular components [29,30]. By contrast, the source of NSAID-induced ROS production is considered to be the mucosal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…8) and inhibited apoptosis (Fig. 6) in RIE-1 cells, it seems that the initial ROS production may have affected intracellular protein function, resulting in the indomethacin-induced This hypochlorous anion reacts with ammonia, derived from urea by H. pylori-associated urease, and yields a cytotoxic oxidant, monochloramine (NH 2 Cl), whose lipophilic properties allow it to freely penetrate biological membranes to oxidize intracellular components [29,30]. By contrast, the source of NSAID-induced ROS production is considered to be the mucosal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The increment in the cis -aconitate level results from the activation of enzyme aconitase, which catalyzes the conversion of citrate to cis -aconitate, and of cis -aconitate to isocitrate. It is reported that H. pylori infection causes accumulation of reactive oxygen species (ROS) in the gastric mucosa [17], and intensification of ROS reduces in turn the activity of aconitase in rat liver [18]. These results imply a modulated energy metabolism in response to oxidative stress in infected mice, which partly explains the elevated glucose.…”
Section: Discussionmentioning
confidence: 99%
“…, and oxidative DNA damage in gastric mucosa in animal and human models (8)(9)(10)(11)(12). ROS production of the blood samples from H. pylori infected subjects was significantly decreased 2 months after eradication (13).…”
Section: Helicobacter Pylori (H Pylori) Is a Gram Negative Bacteriummentioning
confidence: 99%